The Physiological Response of Germination and Growth in Solanaceae Plants (Capsicum frutescens, Solanum melongena, Solanum lycopersicum) at Different Salinity Levels - Nelly Vikiladyla Della; Endah Dwi Hastuti; Nintya Setiari (The University of Lampung, 2024)
High salinity causes osmotic stress and ion imbalance that can reduce plant productivity. Solanaceae can be developed for cultivation in saline land, but its growth is influenced by the type of species. This study aims to examine the tolerance level of three Solanaceae plants to salinity stress through observation of physiological responses of germination and growth. This study used a 3 x 4 factorial Completely Randomized Design (CRD). The first factor is salinity: 0 ppm, 2,500 ppm, 5,000 ppm and 7,500 ppm. The second factor is the Solanaceae species, namely Capsicum frutescens, Solanum melongena, and Solanum lycopersicum. Germination parameters include germination power, wet weight and dry weight. The growth parameters observed include plant height, root length, stem diameter, leaf area, number of leaves, wet weight of leaves, roots and stems and dry weight of leaves, roots and stems. The results of the study showed that C. frutescens is a plant that is more tolerant to salinity up to a concentration of 5,000 ppm when compared to S. melongena and S. lycopersicum whose tolerance is up to 2,500 ppm. Keywords: Germination, Salinity, Solanaceae, Vegetative Growth.